IMPLEMENTASI MODEL GAME-BASED LEARNING DALAM PEMBELAJARAN IPA UNTUK MENINGKATKAN KEAKTIFAN SISWA SD - Muhammad Alfarisi; Andi Widiono; Andriyansah (JURNAL FIRNAS, 2025)
Abstract: This study aims to implement the Game-Based Learning model in improving student activity and learning outcomes in science learning in grade IV of SD N 1 Sidomulyo. Using the classroom action research (CAR) method with two cycles, this study applies the educational game "Light Explorer" for the material on the properties of light in cycle I and "Force and Motion Quest" for the material on force and motion in cycle II. Data were collected through observation, tests, interviews, and student response questionnaires. The results showed a significant increase in student activity from 26.67% (initial condition) to 66.67% (cycle I) and 86.67% (cycle II). Learning outcomes also increased with an average value from 63.60 (initial condition) to 73.87 (cycle I) and 82.53 (cycle II), and classical completeness reached 86.67% in cycle II. The students’ responses were very positive with 93.33% of students showing enthusiasm towards game based learning in cycle II. Supporting factors for successful implementation include game design that suits students’ characteristics, effective collaboration between researchers and teachers, and students’ enthusiasm. Meanwhile, inhibiting factors include time constraints, students’ diverse adaptability, technology limitations, and individual assessment difficulties. This study concludes that Game-Based Learning is an effective model to improve the activeness and science learning outcomes of elementary school students.